Pattern of occurrence and treatment outcome of second primary malignancies: A single center experience - Chaudhary, Prekshi; Gupta, Sweety; Leekha, Nitin; Tandon, Ruchir; Nandy, Malay; De, Sudarsan (South Asian Journal of Cancer, 2017)
Background: The incidence of cancer survivors is increasing, but these individuals, unfortunately, face the risk of second primary malignancies (SPMs). This increasing incidence can be credited to increased survival rates of cancer patients, environmental factors, host factors, and genetic predispositions. Hence, vigilance on the part of the patient as well as clinician for the development of new signs and symptoms is mandatory. Aims: Retrospective analysis of the pattern of incidence and clinical outcome of patients diagnosed with SPM and to review the literature. Settings and Design: A hospital-based retrospective collection of prospective data of patients diagnosed with SPM. Materials and Methods: Thirty-six patients with histopathologically proven SPM from January 2009 to July 2015 were included in this study. Factors such as age, sex, site, stage, histology, treatment received, and outcome were recorded. Statistical Analysis Used: Basic statistical tools have been used for analyzing the data. Results and Conclusions: The likelihood of occurrence of second malignancy, either synchronous or metachronous, should always be kept in mind while evaluating a cancer patient. Appearance of new signs and symptoms during the initial evaluation as well as during follow-up should raise a suspicion, and both patient and oncologist should have a low threshold for further assessment. Early diagnosis and treatment will reduce morbidity and mortality and lead to better survival outcome.
Keywords: Cancer survivors; second primary malignancy; synchronous and metachronous dual malignancy